Expression Of Cox-2 In Non- Liver Diseases - Hashmi, Mubashira; Kehar, Shahnaz Imdad (International Journal of Pathology, 2018)
To determine the frequency of liver diseases and evaluate the expression of COX-2 in non-neoplasticand neoplastic liver lesions.Methodology: This cross sectional study is based on the analysis of liver biopsies received at department ofpathology, BMSI, JPMC from 1st January 2010 to 31st December 2012. Approximately 71 cases of formalin fixed livertissue biopsies were selected and analyzed for morphological features, grading and results ofimmunohistochemical staining for COX-2. The data feeding and analysis were on computer package SPSS(Statistical Packages of Social Sciences) version 16.0. In all statistical analysis only p-value <0.05 was consideredsignificant.Results: The most commonly encountered liver disease , out of the total 288 cases ,was chronic liver disease(CLD) including 255 cases (88.54%) out of these 12(4.17%) showed full- fledged cirrhotic nodule. Mean age was33 yrs. for chronic liver disease. Male female ratio was 1.6:1 for CLD while for hepatocellular carcinoma and bileduct carcinoma M/F ratio was 2.8:1. The etiological distribution of 255 cases of CLD cases revealing that hepatitisC is the most common cause of chronic hepatitis accounting for 70% of cases. On immunostaining using COX-2antibody for CLD with mild inflammatory grade cases, only 14.2% showed strong staining and all the 19 HCCand bile duct carcinoma 78.94% displayed strong positivity.Conclusion: There is progressive increase in staining expression of COX-2 in non-neoplastic and neoplasticliver lesions. An early inhibition of COX-2 via selective COX-2 inhibitors may prevent further exacerbation ofdisease.